2013
DOI: 10.1371/journal.pone.0060015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Variation on the Horse Y Chromosome and the Tracing of Male Founder Lineages in Modern Breeds

Abstract: The paternally inherited Y chromosome displays the population genetic history of males. While modern domestic horses (Equus caballus) exhibit abundant diversity within maternally inherited mitochondrial DNA, no significant Y-chromosomal sequence diversity has been detected. We used high throughput sequencing technology to identify the first polymorphic Y-chromosomal markers useful for tracing paternal lines. The nucleotide variability of the modern horse Y chromosome is extremely low, resulting in six haplotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(114 citation statements)
references
References 50 publications
10
104
0
Order By: Relevance
“…S5.4). This close relationship indicates paternal continuity since the early 19th century and that diverse stallions were incorporated into the makeup of present-day Yakutian horses, in contrast to previous observations in other domesticated horse breeds (29,30). Interestingly, the mid-Holocene specimen Batagai presented a haplotype not described in any present-day horse but closely related to the haplotype of an ∼16,000-y-old stallion from the Taymir Peninsula (Russia; specimen CGG10023) (18), which not only suggests paternal continuity between ancient Yakutian and Taymir populations but also the later extinction and/ or replacement of ancient local males by domestic patrilineages.…”
Section: Resultsmentioning
confidence: 47%
“…S5.4). This close relationship indicates paternal continuity since the early 19th century and that diverse stallions were incorporated into the makeup of present-day Yakutian horses, in contrast to previous observations in other domesticated horse breeds (29,30). Interestingly, the mid-Holocene specimen Batagai presented a haplotype not described in any present-day horse but closely related to the haplotype of an ∼16,000-y-old stallion from the Taymir Peninsula (Russia; specimen CGG10023) (18), which not only suggests paternal continuity between ancient Yakutian and Taymir populations but also the later extinction and/ or replacement of ancient local males by domestic patrilineages.…”
Section: Resultsmentioning
confidence: 47%
“…Y-chromosome haplotypes were recovered by aligning reads against previously identified Y-chromosome contigs (12,75), first against the contigs alone and then remapped against the full nuclear genome, including the Y-chromosome contigs, to control for repetitive regions. Mapping and genotyping were as described above, except that a minimum depth of 4 and a maximum depth of 50 were used when filtering SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…In horses, however, the assembly for the whole NRY region is not available yet, as the reference genome was characterized from a single mare individual (Wade et al 2009). Studies targeting specific NRY regions have shown limited variation, with haplotypes differing by one mutational step at best, which indicates that only a handful of paternal lines survived until present-day in domestic horses (Lindgren et al 2004;Brandariz-Fontes et al 2013;Wallner et al 2013;Kreutzmann et al 2014;Han et al 2015). By contrast, analyses initially based on the mtDNA control region (D-loop) (Lister et al 1998;Vilà et al 2001;Jansen et al 2002;Cieslak et al 2010), and more recently on complete mitochondrial genomes (Lippold et al 2011a;Achilli et al 2012), revealed horses as the domestic animal showing one of the largest pools of mitochondrial genetic diversity.…”
Section: Gender-biased Contributions To Domesticationmentioning
confidence: 99%
“…Although this could partly result from the horse polygamous mating system, the sequence diversity found in ancient wild horses suggests that current levels of variability cannot be explained without a sex-biased contribution to the domestic stock (Lippold et al 2011b). More specifically, the decline in NRY diversity appears to be a domestication by-product, perhaps as a result of recent breeding programs aimed at producing valuable stallions for rural regions, as (i) the only Scythian horse sampled, dating to 2.8 KYA, exhibits an NRY haplotype different from that found in modern individuals (Lippold et al 2011b); and (ii) pedigree-based analyses can trace the most common patrilines back to a few, but extremely influential, stallions that lived 200 years ago (Wallner et al 2013). Only the Yakutian breed is known to display substantial levels of NRY diversity , probably because it originated in the 13th to 15th century, following the migration of Mongolian tribes to the Sakha Republic (Russia) (Pakendorf et al 2006;Crubézy et al 2010).…”
Section: Gender-biased Contributions To Domesticationmentioning
confidence: 99%